Translation regulation in plants: an interesting past, an exciting present and a promising future. (30th March 2017) - Merchante, Catharina; Stepanova, Anna N.; Alonso, Jose M.
Summary: Changes in gene expression are at the core of most biological processes, from cell differentiation to organ development, including the adaptation of the whole organism to the ever‐changing environment. Although the central role of transcriptional regulation is solidly established and the general mechanisms involved in this type of regulation are relatively well understood, it is clear that regulation at a translational level also plays an essential role in modulating gene expression. Despite the large number of examples illustrating the critical role played by translational regulation in determining the expression levels of a gene, our understanding of the molecular mechanisms behind such types of regulation has been slow to emerge. With the recent development of high‐throughput approaches to map and quantify different critical parameters affecting translation, such as RNA structure, protein–RNA interactions and ribosome occupancy at the genome level, a renewed enthusiasm toward studying translation regulation is warranted. The use of these new powerful technologies in well‐established and uncharacterized translation‐dependent processes holds the promise to decipher the likely complex and diverse, but also fascinating, mechanisms behind the regulation of translation. Significance Statement: Regulation at the translational level is an important point in the control of gene expression. Here we review examples of translation regulation studies in plants. We highlight new technologies such as Ribo‐Seq and Structure‐Seq that can be used to mechanistically understand how plants regulate translation under different conditions as well as the consequences of perturbing such mechanisms.